The Relationship between Instant Noodle Consumption and Dental Caries in a Boarder in Medan, Indonesia - Parluhutan Hutagalung, Mangatas Halomoan; Susiani Tarigan; Suryati Sinurat; Maghfirah Muchtar (HM Publisher, 2024)
This research is motivated by the fact that food, as a food substrate, plays an important role in the development of dental caries. Carbohydrates, fats, and proteins are the main components of the human diet. One of the most effective and cheap fast foods is instant noodles. Consuming instant noodles for a long period of time and not having your teeth checked regularly by going to the dentist can result in various problems in the oral cavity. This research looks at the relationship between instant noodle consumption and caries in a boarder in the city of Medan in 2023. The type of research used includes observational analytics. The results of the research show that most children have consumption habits of instant noodles in the medium category, namely 7 boarders. Most boarders had a caries incidence in the medium category with a total of 9 boarders. Therefore, it is concluded that there is a relationship between the habit of consuming instant noodles and dental caries. The higher the habit of consuming instant noodles, the higher the potential for dental caries.